Community Perception of the Traditional Custom of Replacing the Roof of the Raja's House in Hitu Village, Leihitu District, Central Maluku Regenc - Uwen, Aldi; Lasaiba, Mohammad Amin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
This study examines the community's perception of the traditional custom of replacing the roof of the Raja's house in Hitu Village, Leihitu District, Central Maluku Regency, Indonesia. The research focuses on various aspects of this tradition, including the size and placement of the roof, changes in objects, and the repetition process. The research method used is descriptive, with data collected through field observations, interviews, and documentation. The findings indicate that the traditional custom of replacing the roof of Raja's households has cultural, social, and economic significance. The community closely adheres to this tradition, preserving values of togetherness, mutual respect, and cooperation. Beyond cultural values, this tradition also has a positive impact on local tourism and the economy. It is not merely a ceremonial event but also serves as a means to maintain cultural identity, strengthen community bonds, and provide economic opportunities for the local population. Highlighting regional culture through such traditions has the potential to become a unique tourist attraction. In conclusion, the traditional custom of replacing the roof of Raja's house in Hitu Village is a manifestation of cultural sustainability that has broad impacts, involving community participation and offering economic and tourism opportunities for the area.